Non-Coding RNA Mediated Regulation of Allogeneic T Cell Responses After Hematopoietic Transplantation - Peltier, Daniel; Reddy, Pavan (Frontiers in Immunology, 2018)
Allogeneic bone marrow transplantation (BMT) is an effective therapy for several malignant and non-malignant disorders. The precise control of allogeneic T-cells is critical for successful outcomes after BMT. The mechanisms governing desirable (graft versus leukemia) versus undesirable (graft versus host disease) allogeneic responses remain incompletely understood. Non-coding RNAs (ncRNA) are controllers of gene expression that fine-tune cellular responses. Multiple micro-RNAs (miRNA), a type of ncRNA, have recently been shown to influence allogeneic T cell responses in both murine models and clinically. Here we review the role of various microRNAs that regulate T cell responses, either positively or negatively, to allo-stimulation and highlight their potential relevance as biomarkers and as therapeutic targets for improving outcomes after allogeneic BMT.